C‐MYC expression and maturity phenotypes are associated with outcome benefit from addition of ixazomib to lenalidomide‐dexamethasone in myeloma. (15th April 2020) - Di Bacco, Alessandra; Bahlis, Nizar J.; Munshi, Nikhil C.; Avet‐Loiseau, Hervé; Masszi, Tamás; Viterbo, Luísa; Pour, Ludek; Ganly, Peter; Cavo, Michele; Langer, Christian; Kumar, Shaji K.; Rajkumar, S. Vincent; et al.
Abstract: Objectives: In the TOURMALINE‐MM1 phase 3 trial in relapsed/refractory multiple myeloma, ixazomib‐lenalidomide‐dexamethasone (IRd) showed different magnitudes of progression‐free survival (PFS) benefit vs placebo‐Rd according to number and type of prior therapies, with greater benefit seen in patients with >1 prior line of therapy or 1 prior line of therapy without stem cell transplantation (SCT). Methods: RNA sequencing data were used to investigate the basis of these differences. Results: The PFS benefit of IRd vs placebo‐Rd was greater in patients with tumors expressing high c‐MYC levels (median not reached vs 11.3 months; hazard ratio [HR] 0.42; 95% CI, 0.26, 0.66; P  < .001) compared with in those expressing low c‐MYC levels (median 20.6 vs 16.6 months; HR 0.75; 95% CI, 0.42, 1.2). Expression of c‐MYC in tumors varied based on the number and type of prior therapy received, with the lowest levels observed in tumors of patients who had received 1 prior line of therapy including SCT. These tumors also had higher expression levels of CD19 and CD81. Conclusions: PFS analyses suggest that lenalidomide and ixazomib target tumors with different levels of c‐MYC, CD19, and CD81 expression, thus providing a potential rationale for the differential benefits observed in the TOURMALINE‐MM1 study. This trial was registered at www.clinicaltrials.gov as: NCT01564537